2014
DOI: 10.7314/apjcp.2014.15.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants at 6p21.1 and 7p15.3 Identified by GWASs of Multiple Cancers and Ovarian Cancer Risk: a Case-control Study in Han Chinese Women

Abstract: A recent study summarized several published genome-wide association studies (GWASs) of cancer and reported two pleiotropic loci at 6p21.1 and 7p15.3 contributing to multiple cancers including lung cancer, noncardia gastric cancer (NCGC), and esophageal squamous-cell carcinoma (ESCC) in Han Chinese. However, it is not known whether such genetic variants have similar effects on the risk of gynecologic cancers, such as ovarian cancer. Hence, we explored associations between genetic variants in 6p21.1 and 7p15.3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…The p38 MARK pathway plays an additional role in the induction of the immune and inflammatory responses [23,24] as well as in the regulation of cell differentiation, migration and survival [25,26]. Li found that rs2285947 was associated with increasing ovarian cancer risk in Han Chinese women and this result was consistent with Jin [14]. However, in this case-control study, we failed to observe any significant association of this SNP with risk of HNC or subgroup of HNC, suggesting rs2285947 may not contribute to the risk of HNC, but we could not completely exclude the possibility that the association between 7p15.3 variants and HNC risk and our analysis did not have enough statistical power to detect it.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The p38 MARK pathway plays an additional role in the induction of the immune and inflammatory responses [23,24] as well as in the regulation of cell differentiation, migration and survival [25,26]. Li found that rs2285947 was associated with increasing ovarian cancer risk in Han Chinese women and this result was consistent with Jin [14]. However, in this case-control study, we failed to observe any significant association of this SNP with risk of HNC or subgroup of HNC, suggesting rs2285947 may not contribute to the risk of HNC, but we could not completely exclude the possibility that the association between 7p15.3 variants and HNC risk and our analysis did not have enough statistical power to detect it.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, Jin et al utilized the existing GWAS data on lung cancer, noncardia gastric cancer (NCGC) and esophageal squamous-cell carcinoma (ESCC) to map pleiotropic loci contributing to these three types of cancer in Han Chinese populations, and identified 2 novel SNPs (rs2494938 at 6p21.1 and rs2285947 at 7p15.3) significantly associated with all three types of cancer [13]. Additionally, Li found that rs2285947 at 7p15.3 also contribute to the development of ovarian cancer in Han Chinese women [14]. These findings indicate rs2494938 at 6p21.1 located in the intron region of LRFN2 [MIM 612808] and rs2285947 at 7p15.3 located in the intron of DNAH11 [MIM 603339] are candidate susceptibility loci for multiple types of human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, evidences have confirmed the association of the polymorphism rs2285947 in DNAH11 with the higher risk of human cancers, such as ovarian cancer, head and neck cancer, lung cancer, non-cardia gastric cancer and esophageal squamous cell carcinoma [14, 26, 27]. We found that the GA/AA genotype of rs2285947 exhibited a significant association with poorer survival than the GG genotype among ESCC patients.…”
Section: Discussionsupporting
confidence: 57%
“…6q24.1, breast cancer, neuroblastoma, melanoma (63); chr. 7p15.3, ovarian cancer (64,65); chr. 8q24.21, leukemia/lymphoma (66,67); chr.…”
Section: Discussionmentioning
confidence: 99%